Patterns of Social Integration Strategies: Mobilising ‘Strong’ and ‘Weak’ Ties of the New European Migrants - Popivanov, Boris (Social Inclusion, 2019)
The European mobility processes raise the issue of the integration strategies of new European migrants in their host societies. Taking stock of 154 in-depth interviews with migrants in the UK, Germany, Italy and Spain, we examine the social ties which they mobilise in order to adapt in a different social environment. The division between ‘strong’ and ‘weak’ ties established in the literature is particularly useful to assess migrants’ experiences in appropriation and transformation of social capital and the variety of their pathways in the labour market. Then we critically study the relative weight of social ties and skill levels in their choice of integration strategies. At the end, four types of strategies corresponding to the types of migrants’ interactions with the home and host contexts are outlined.